Application of the Project Based Learning (PjBL) Model on the Concept of Global Warming to Improve Students' Knowledge of State Senior High School 1 Bandar Bener Meriah - Dewi Murni; Jailani; Nurul Akmal; Evi Apriana; Fakhrurrazi (Jurnal Penelitian Pendidikan IPA, 2026)
Project Based Learning (PjBL) is a learning model that emphasizes active student involvement in the learning process through contextual and meaningful project activities. This study aims to analyze the application of the Project Based Learning (PjBL) model to the concept of global warming and its impact on the knowledge of tenth-grade students. This study used a quantitative approach with a quasi-experimental method and a pretest–posttest control group design. The research sample consisted of two classes: class IA X-1 with 22 students as the experimental class and class IA X-2 with 21 students as the control class, resulting in a total sample of 43 students. The experimental class was given treatment in the form of learning using the PjBL model, while the control class used conventional learning. The research instrument was a knowledge test administered before and after the treatment. Data were analyzed using descriptive statistics and N-Gain calculations. The results showed that there was a difference in knowledge gain between the experimental and control classes. The increase in student knowledge in the experimental class was higher than in the control class, with the N-Gain results being in the moderate to high category. Based on these results, it can be concluded that the implementation of the Project Based Learning (PjBL) model is effective in increasing student knowledge on the concept of global warming.